Parameters Affect Flexural Mechanism to Prevent Progressive Collapse of RC Buildings - Z.M. Najem; Thaer Alrudaini (Electronic Journal of Structural Engineering, 2023)
This study investigates the effect of spans length, reinforcement ratio and continuity of flexural reinforcement on the progressive collapse performance of double span beams over failed columns. The investigations focus on initial flexural resisting mechanism to prevent the progressive collapse. Detailed nonlinear finite element simulation of double span beam-column sub-assemblages subjected to residual gravity loads that initially carried by the failed column is adopted for the investigations. Nonlinear static pushover analysis is conducted in which capacity curves are derived and compared with demanded capacities. The effect of spans length, reinforcement ratio and number of continuous bottom flexural reinforcement on progressive collapse are considered in the investigations. Analysis results show that the strength to resist progressive collapse has decreased by 25.4 % and the ductility increased by 103 % following the increasing in span length from 5 m to 7 m. On the other hand, increasing reinforcement ratio of top flexural reinforcement from 0.447 to 1.089 leads to 26.27 % increasing in strength accompanied with a decrease in ductility equal to 16.42 %. In addition, extending all bottom bars rather than the minimum specified two bars resulted in 12 % increasing in strength and 40.28 % decreasing in ductility.